Critical Realism in Context - Porter, Stanley E. (Journal for the study of the historical Jesus, 2015)
N.T. Wright’s critical realist epistemology has become the foundation for many recent studies of Christian origins. This article argues that New Testament scholars have perhaps too quickly and uncritically adopted this method, when it is out of step with contemporary analytic epistemology. The method Wright employs—and which many have adopted—originates with an internalist epistemic account developed in the 1940s. Since then, key developments in the study of epistemology (beginning with Gettier in 1963) have made Wright’s critical realist model irrelevant in many ways. In light of these inadequacies, we tentatively outline some potential components of a more promising historical epistemology for the study of Christian origins.